The Community Service Journal Socialization of Safety Riding and School Save Zones (ZOSS), in SMPN 3 Mande, Jamali Village - Cianjur : Socialization of Safety Riding and School Save Zones (ZOSS), in SMPN 3 Mande, Jamali Village - Cianjur - Marlita, Devi; Lesmini, Lis; Indriyati, Indriyati; Handayani, Sri; Saribanon, Euis (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
The Community Service Program (PKM) by ITL Trisakti aims to improve student driving safety through the socialization of Safety Riding and the implementation of the School Safe Zone (ZOSS). This activity involved students of SMPN 3 Mande, Jamali Village, as the main participant. Through an educational approach, this program provides technical training on safe driving and infrastructure improvements around schools. The results of the activity showed an increase in student understanding from 50% in the pre-test to 90% in the post-test. This program is expected to reduce the number of accidents and create a safe driving culture among students. This activity has a significant positive impact on students' understanding of driving safety. This activity not only increases students' knowledge but also forms their awareness of the importance of applying safety principles in daily life. This activity succeeded in increasing the understanding of SMPN 3 Mande students about Safety Riding and ZOSS. This is evidenced by an increase in post-test scores by 40% compared to pre-test results. The interactive socialization method has proven to be effective in providing driving safety education. The use of visual media, interactive discussions, and question and answer sessions make it easier for students to understand the material. Jamali Village has great potential to be an example of successful ZOSS implementation. Support from schools, communities, and students can strengthen the implementation of ZOSS in a sustainable manner. ABSTRAK Program Pengabdian Kepada Masyarakat (PKM) oleh ITL Trisakti bertujuan meningkatkan keselamatan berkendara siswa melalui sosialisasi Safety Riding dan implementasi Zona Selamat Sekolah (ZOSS). Kegiatan ini melibatkan siswa SMPN 3 Mande, Desa Jamali, sebagai peserta utama. Melalui pendekatan edukatif, program ini memberikan pelatihan teknis berkendara aman serta perbaikan infrastruktur di sekitar sekolah. Hasil kegiatan menunjukkan peningkatan pemahaman siswa dari 50% pada pre-test menjadi 90% pada post-test. Program ini diharapkan dapat mengurangi angka kecelakaan dan menciptakan budaya berkendara aman di kalangan pelajar. Kegiatan ini memberikan dampak positif yang signifikan terhadap pemahaman siswa mengenai keselamatan berkendara. Kegiatan ini tidak hanya meningkatkan pengetahuan siswa tetapi juga membentuk kesadaran mereka akan pentingnya menerapkan prinsip-prinsip keselamatan dalam kehidupan sehari-hari. Kegiatan ini berhasil meningkatkan pemahaman siswa SMPN 3 Mande tentang Safety Riding dan ZOSS. Hal ini dibuktikan dengan adanya peningkatan skor post-test sebesar 40% dibandingkan dengan hasil pre-test. Metode sosialisasi interaktif terbukti efektif dalam memberikan edukasi keselamatan berkendara. Penggunaan media visual, diskusi interaktif, dan sesi tanya jawab membuat siswa lebih mudah memahami materi. Desa Jamali memiliki potensi besar untuk menjadi contoh penerapan ZOSS yang berhasil. Dukungan dari pihak sekolah, masyarakat, dan siswa dapat memperkuat implementasi ZOSS secara berkelanjutan.